ADDRESSING THE GAP: A NEED FOR A GENDER-BASED APPROACH IN INDONESIA’S DERADICALIZATION PROGRAM - Mutiara, Raneeta (UI Scholars Hub, 2024)
An effective deradicalisation program is the key to combating violent extremism and reducing potential harm to society from radical ideologies. A gender-based approach to tackling violent extremism among women has received esteemed recognition from the governments of many countries. Various international organizations and scholarly institutes have also approved the advantages of this method. This work aims to find and address the gap in the current deradicalization program in Indonesia for future development in both academic and practical areas of this subject matter. An integrative literature review is used as a method that involves synthesizing previous research and integrating empirical findings and perspectives to uncover areas where more research is needed. Through a substantial amount of literature considered in this work, Indonesia’s deradicalization program is discovered to lack a gender perspective. The ingrained patriarchy and male-centric attitude are identified as the primary reasons behind its unpopularity. Evidence from various case studies has been provided to justify the gap and the need to integrate a gender-based approach into the deradicalization program in Indonesia. Recommendations include recruiting more female deradicalization experts, providing specialized training to female prison officers to counter violent ideology, and tightening collaboration with women-based civil society organizations.